2007
DOI: 10.1123/japa.15.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Exercise Behavior: Roles of Selected Constructs of Social-Cognitive Theory

Abstract: Exercise is consistently related to physical and psychological health benefits in older adults. Bandura’s social-cognitive theory (SCT) is one theoretical perspective on understanding and predicting exercise behavior. Thus, the authors examined whether three SCT variables—self-efficacy, self-regulation, and outcome-expectancy value—predicted older adults’ (N= 98) exercise behavior. Bivariate analyses revealed that regular exercise was associated with being male, White, and married; having higher income, educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…These findings also support evidence in the literature noting the importance of verbal persuasion in understanding Social Cognitive Theory (Bandura, 1997) as it relates to the development of self-efficacy in activities such as adherence to exercise programs (Bock, Marcus, Pinto, and Forsyth, 2001;Brassington et al, 2002;Cromwell and Adams, 2006;Dallow and Anderson, 2003;O'Hea et al, 2004;Umstattd and Hallam, 2007;Wilbur, Chandler, and Miller, 2001). These participants described positive results from physical therapy and the development of a sense of trust in staff, and the expertise and credibility of others have been identified as important determinants of self-efficacy (Arora, Ayanian, and Guadagnoli, 2005).…”
Section: Client Similaritiessupporting
confidence: 80%
See 2 more Smart Citations
“…These findings also support evidence in the literature noting the importance of verbal persuasion in understanding Social Cognitive Theory (Bandura, 1997) as it relates to the development of self-efficacy in activities such as adherence to exercise programs (Bock, Marcus, Pinto, and Forsyth, 2001;Brassington et al, 2002;Cromwell and Adams, 2006;Dallow and Anderson, 2003;O'Hea et al, 2004;Umstattd and Hallam, 2007;Wilbur, Chandler, and Miller, 2001). These participants described positive results from physical therapy and the development of a sense of trust in staff, and the expertise and credibility of others have been identified as important determinants of self-efficacy (Arora, Ayanian, and Guadagnoli, 2005).…”
Section: Client Similaritiessupporting
confidence: 80%
“…They also expressed having a sense of comfort in the knowledge that their physical therapists were available at the same area for consultation if needed. Collectively, these types of client responses regarding participation in the aftercare programs are consistent with constructs within Bandura's Social Cognitive Theory as it relates to positive behavioral changes, substantiating the importance of factors such as positive reinforcement and environment in fostering desired health behaviors (Bandura, 1997;Bock, Marcus, Pinto, and Forsyth, 2001;Brassington et al, 2002;Cromwell and Adams, 2006;Dallow and Anderson, 2003;McCloy, 2001;O'Hea et al, 2004;Umstattd and Hallam, 2007;Wilbur, Chandler, and Miller, 2001).…”
Section: Client Similaritiesmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, physical activity was measured by a self-report questionnaire, which might be subject to some measurement error. While the relationship between self-regulation for physical activity and physical activity using GPAQ could not be investigated through any previous study, reported values of the correlation varied among previous studies 14 - 16) , 21) . These results possibly depended on scales used to assess physical activity.…”
Section: Discussionmentioning
confidence: 93%
“…We also hypothesized that scores of the PASR-12 would positively correlate with physical activity ( r ≥ 0.20) and self-efficacy for physical activity ( r ≥ 0.30). These hypothesized effect sizes were estimated from previous studies 14 - 16) , 21) in which the correlation coefficients ( r ) between self-regulation and physical activity ranged from -0.03 to 0.85 ( M = 0.23), and those between self-regulation and self-efficacy ranged from 0.11 to 0.79 ( M = 0.32; COSMIN boxes F-4, F-5, F-6).…”
Section: Introductionmentioning
confidence: 99%